A man escaped, or, the wind blows where it wishes [videorecording (DVD)] = Un condamné à mort s'est échappé, ou, Le vent souffle où il veut - Bresson, Robert; Bresson, Robert; Leterrier, François; Le Clainche, Charles; Beerblock, Maurice; Monod, Roland; Ertaud, Jacques, 1924-1995; Devigny, André, 1916-1999 (Criterion collection, 2013)
Based on the memoirs of an imprisoned French resistance leader, this unbelievably taut and methodical marvel follows the fictional Fontaine's single-minded pursuit of freedom, detailing the planning and carrying out of his escape with gripping precision.